Lung ultrasound imaging can effectively monitor and guide treatment with pulmonary surfactant for preterm infants of pulmonary consolidation: a prospective observational cohort study - Zaili, Feng; Na, Huang (Frontiers in Pediatrics, 2025)
BackgroundA radiation-free method for dynamic evaluation of infant lung function is lung ultrasound (LUS).ObjectiveTo assess if LUS-guided surfactant therapy, which is based on direct observation of pulmonary consolidation, is an effective way to guide treatment timing and dosage in preterm infants (less than 34 weeks of gestation).MethodsThis prospective observational cohort study was conducted at Dehong Hospital affiliated to Kunming Medical University, in various clinical settings, including newborn wards, neonatal intensive care units (NICUs), obstetric operating rooms and delivery rooms. Within an hour of delivery, all preterm newborns received their first LUS. The frequency of monitoring was adjusted for those without consolidation at various intervals; if consolidation was detected, PS[Poractant alfa (Curosur®; Chiesi Farmaceutici S.p.A., Italy)] 200 mg/kg was administered immediately. A repeating dose of 100 mg/kg was administered if consolidation did not go away after 12 h. Following each PS treatment, LUS assessments were conducted every four hours, and monitoring was progressively decreased once consolidation was resolved. PS was not administered to TTN preterm newborns without consolidation. The frequency of PS administration, the prevalence of pulmonary consolidation, and the number of infants who had complete lung re-expansion were also noted.ResultsWith each PS dose, the rate of complete lung re-expansion among infants with neonatal respiratory distress syndrome (NRDS, n = 55) increased significantly (first dose: 60.0%, second dose: 63.6%, third dose: 75.0%; trend χ2 = 102.45, P < 0.001), with 96.4% of infants achieving complete re-expansion within three doses. On the other hand, regardless of dose escalation, children with transient tachypnea of the newborn (TTN, n = 37) achieved complete lung recruitment in 2 doses (P = 0.482), and all TTN infants eventually attained complete recruitment. The frequency of LUS examinations varied by clinical context, with the neonatal room having the lowest frequency (9.70%) and the obstetric operating room having the highest frequency (38.70%).ConclusionIn preterm newborns, NRDS and TTN can be effectively managed using LUS-guided PS therapy based on consolidation monitoring. While TTN can be treated with a fixed-dose regimen, NRDS has a dose-response relationship that supports customized dosage. The frequency and timing of surfactant administration in preterm newborns are determined by LUS-detected lung consolidation, which also acts as a decision-making indicator for PS therapy.